Low-grade epilepsy-associated neuroepithelial tumours - the 2016 WHO classification - Blümcke, Ingmar; Aronica, Eleonora; Becker, Albert; Capper, David; Coras, Roland; Honavar, Mrinalini; Jacques, Thomas S.; Kobow, Katja; Miyata, Hajime; Mühlebner, Angelika; Pimentel, José; Söylemezoğlu, Figen; et al. (Nature reviews. Neurology, 2016)
The recently revised 5th edition of the WHO classification of brain tumours 'blue book' will have a major impact in stratifying diagnosis and treatment. However, low-grade neuroepithelial tumours (LEATs), which present with early-onset focal epilepsy, lack integrated clinicopathological and molecular genetic diagnostic tools. The Neuropathology Task Force of the International League against Epilepsy will critically discuss this issue, as well as offer perspectives on how to decipher and validate clinically meaningful LEAT entities using the current WHO approach.
Gesehen am 13.05.2020